A novel PCR-based point-of-care method facilitates rapid, efficient, and sensitive diagnosis of influenza virus infection. (August 2019) - Schmidt, R.L.J.; Simon, A.; Popow-Kraupp, T.; Laggner, A.; Haslacher, H.; Fritzer-Szekeres, M.; Redlberger-Fritz, M.; Mayer, F.J.
Abstract: Objective: The aim of this single-centre study was the comparative analysis of the GeneXpert (Cepheid Inc.) and the LIAT (Roche) system for the rapid polymerase chain reaction (PCR)-based detection of influenza A (IA) and influenza B (IB) viruses. Patients and methods: During the 2017–2018 flu season, 651 prospectively collected samples (throat and nasal swabs) of patients with symptoms of influenza-like illness or acute respiratory infection were tested for the presence of IA and IB viruses using the GeneXpert and LIAT systems. To evaluate the usefulness for near-patient testing, a LIAT system was installed at the Department of Emergency Medicine, and sample testing was performed on site. Reference testing of all samples was performed with the Xpert Flu assay and for 313 samples in addition with the Xpert Xpress Flu/RSV (respiratory syncytial virus) assay at the central laboratory. Analysis of all samples was carried out within 24 hr after collection. Results: Overall, 267 of the 651 samples analysed were positive for influenza viruses in at least one of the three assays investigated (IA, 88; IB, 179). The overall rates of agreement between the LIAT assay and the Xpert Flu assay was 96.0% for the detection of IA and IB viruses. The sensitivity and specificity of the LIAT assay compared to the Xpert Flu assay for the detection of IA was 98.80% (95% confidence interval (CI) 93.47–99.97%) and 99.12% (95% CI, 97.96% to 99.71%) and for the detection of IB 98.76% (95% CI 95.58–99.85%), and 96.33% (95% CI 94.26–97.81%), respectively. The LIAT assay showed a statistically significant higher detection rate of IB virus than the Xpert Flu assay (p <0.01). No significant difference was found between the detection rate of the LIAT assay and the Xpert Xpress Flu/RSV assay. The mean time to the availability of a definite test result was significantly shorter with the on-site LIAT system than the GeneXpert system (mean 59 min saving time; p <0.01). Conclusion: The LIAT system represents a robust and highly sensitive point-of-care device for the rapid PCR-based detection of influenza A and influenza B viruses.